(untitled) (Salam International Academic Journal, 2025)
The migration of Afghan scholars and academics has intensified in recent decades due to imposed wars, political instability, insecurity, and religious, social, and cultural restrictions. This migration, often occurring under coercion and in response to threats to personal safety or professional limitations, has resulted in the loss of valuable human capital from the country. Afghan scholars, university professors, researchers, and experts have relocated to neighboring and distant countries in pursuit of academic continuity and personal security. Although the phenomenon of elite migration has persisted for many years, the Islamic Emirate of Afghanistan must take serious steps to address its negative consequences and mitigate the trend by leveraging the current security environment. While the migration of scholars has created opportunities for international academic engagement, it has also inflicted significant harm on the country’s educational and research systems. Consequences such as brain drain, weakened academic institutions, and the shortage of qualified mentors require urgent attention from national authorities. Supporting migrant scholars and facilitating their return and reintegration into the academic rebuilding process is essential for the country’s intellectual and institutional revival.